The Impact of Language Learning Strategies on Students' English Ability - Elmy Rusdiah Pohan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the effect of language strategies on students' English language skills. This research method is quantitative. This study was conducted at SMP Negeri 1 Sibuhuan, with a sample population of 27 students in grade VIII. Data were taken using a questionnaire, with data analysis techniques using descriptive statistics and simple linear regression tests using normality tests, multicollinearity tests and hypothesis tests. The results of this test were assisted by the SPSS application. The results found that based on the normality test, the significance value was 0.863> 0.05. Then the multicollinearity value at the tolerance value was 0.020 <0.100. The VIF value was 12,000> 10,000. In the hypothesis test, the F value was 12.645 with a significance value of 0.000<0.05.